Gender Differences in Self Acceptance among Economically Disadvantaged Senior High School Students in Bukittinggi, West Sumatera, Indonesia: English - Fella Hanna; Rezki Hariko (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Self-acceptance issues can affect students’ developmental tasks and their ability to adapt within educational environments. This study aimed to analyze the level of students’ self-acceptance and to examine differences in self-acceptance between male and female students from underprivileged backgrounds. The study employed a quantitative approach with a comparative research design. The participants involved high school students from underprivileged families selected through a total sampling technique. Data were collected through the administration of a Self-Acceptance Scale developed based on a Likert-scale model in accordance with indicators of self-acceptance. Data analysis was conducted descriptively by considering measures of central tendency and data distribution, while difference analysis was performed using the independent sample t-test. The findings revealed that students’ self-acceptance was generally categorized as high for both male and female students. The results also indicated that there was no significant difference in self-acceptance based on gender, suggesting that gender was not a major factor influencing the self-acceptance of students from underprivileged backgrounds. This study implies the importance of the role of guidance and counseling teachers in designing sustainable services that support the development of students’ self-acceptance through preventive, developmental, and psychological assistance programs within the school environment.